Implementación de un circuito de video para vigilancia en el edificio del Nivel Técnico. - Vázquez Minchala, Bladimir Alejandro (2009)
In recent years, technology has experienced spectacular breakthroughs, the development of science and technology has been noticed in all aspects of life. It has been rightly said that mankind has undergone deeper changes in the last hundred years than in all the rest of man's history on earth. We see how every day the world revolves around technology and therefore to the automation of everything that has become possible with the different tools for the development, welfare and protection of the human being. The use and implementation of surveillance systems (Closed Circuit Television) in today's society are used to safeguard the security of citizenship, and in our case the university area, because it confers truth to the facts. In the modern control architecture of the current buildings, the incorporation of the surveillance video circuit or Closed Circuit Television (CCTV) is indispensable as a technical means to control the security in its facilities. Projects of this type include night and daytime operation, internal, external cameras and infrared capture for critical safety zones. Among the different types of cameras and the resolution to be presented, a variety of possibilities are proposed, depending on the architecture of the building, its zoning and control possibilities. These equipments include: camera position control mechanisms, approach controls, signal controllers, etc. All these processes can today be controlled by the applied software, and even use the most common installed networks such as Ethernet, optical fibers and even the electrical network of the building to transmit the video signals. CCTV systems basically consist of a series of cameras, fixed or moving, hidden or discreet connected to capture cards or recording devices. In the National University of Loja, specifically in the Energy Area, Industries and Non-Renewable Natural Resources, in the Technical Level building, do not have a security system of this type, and because it is located in this area library , It would be very important and useful the installation of the same, so that the security managers of the building, would have support and support to carry out their work. It is the goal of the following report to show what are the characteristics of CCTV systems, their constitution, applications and the development of some of the technologies used in the structure of a CCTV system such as CCD cameras that make them more efficient and effective .